Ainda sobre os impropriamente chamados "ídolos de cornos" do Neolítico e do Calcolítico da Estremadura e do Sudoeste - Cardoso, João Luís (2017)
There has been some debate over the functionality of some solid clay elements which were usual in settlements of the Final Neolithic and, especially, the Chalcolithic in the Estremadura and in the South of Portugal. These cylinder or cone shaped pieces, usually of rough and half-baked clay and frequently showing signs of fire on the surface, present a variety of types. For some people their household utility function is obvious, as "fireplace supports"; others believe they are above all ritual and symbolic. The author summarises the history of this problem and comments on recent findings.